2016
DOI: 10.1177/1715163516649621
|View full text |Cite
|
Sign up to set email alerts
|

Applying the guidelines for pharmacists integrating into primary care teams

Abstract: Background: In 2013, Jorgenson et al. published guidelines for pharmacists integrating into primary care teams. these guidelines outlined 10 evidencebased recommendations designed to support pharmacists in successfully establishing practices in primary care environments. the aim of this review is to provide a detailed, practical approach to implementing these recommendations in real life, thereby aiding to validate their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Being highly visible and accessible is an important part of integrating pharmacists into primary care in order to ensure success. [4][5][6] It has been suggested that proximity allows for improved team-based care, 7 as demonstrated by the higher numbers of referrals and consultations when the pharmacists are in the physician offices. Further analysis of this effect on the health care system is required, as health outcome data were not collected during this pilot, but the literature has shown that consultation with a pharmacist can result in better health outcomes 8,9 and reduce health care costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being highly visible and accessible is an important part of integrating pharmacists into primary care in order to ensure success. [4][5][6] It has been suggested that proximity allows for improved team-based care, 7 as demonstrated by the higher numbers of referrals and consultations when the pharmacists are in the physician offices. Further analysis of this effect on the health care system is required, as health outcome data were not collected during this pilot, but the literature has shown that consultation with a pharmacist can result in better health outcomes 8,9 and reduce health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Many primary care pharmacists function directly in the same clinic or building with physicians. [4][5][6] Prior to 2013, 2 pharmacists were deployed to each individual NYFHT physician office, spending half a day to a full day, on a weekly to monthly basis. This led to inefficiency due to travel times as well as scheduling difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…When starting new practices, primary care pharmacists often use case-finding strategies to identify patients for pharmacist involvement 22,24 ; however, given the design of the Home Care Program's electronic medical records system, this approach was not feasible. Reliance on referrals, instead of seeking out at-risk patients, may have hampered the full implementation of pharmacist services: early in the pilot period, the team was less aware of the full scope of pharmacist care, indicated by the fact that 23.4% of the initial referrals were requests to print out the patient's medication history.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive strategies that were used during this pilot program did not translate into referrals for the pharmacist, contrary to the success that has been described in primary care pharmacy. 22,24 While some pharmacist activities can be classified using the acute care cpKPI measures, it may be of more value to identify specific cpKPIs for ambulatory care. For example, pharmaceutical care planning could be further distilled into chronic disease management, acute issue resolution, drug procurement, and other aspects of care.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Recently, the Canadian Pharmacists Journal published guidelines for integrating pharmacists into primary care teams and how to apply these guidelines in practice. 18,19 Because pharmacists in primary care clinics do not have a consistent source of patients for whom to provide care (such as patients attending a community pharmacy or patients admitted to a hospital unit), they primarily rely on referrals from other providers to identify patients who may benefit from pharmacy services. However, there are a variety of ways by which a primary care pharmacist may generate referrals, including direct referrals from other clinicians (e.g., physicians, nurses, other pharmacists), questionnaires (e.g., Medication Risk Assessment Questionnaire [MRAQ]), chart reviews or patient self-referrals.…”
Section: Arden R Barrymentioning
confidence: 99%